2022
DOI: 10.1093/nar/gkac046
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the ancient eukaryotic ribosome from the human parasite Giardia lamblia

Abstract: Giardiasis is a disease caused by the protist Giardia lamblia. As no human vaccines have been approved so far against it, and resistance to current drugs is spreading, new strategies for combating giardiasis need to be developed. The G. lamblia ribosome may provide a promising therapeutic target due to its distinct sequence differences from ribosomes of most eukaryotes and prokaryotes. Here, we report the cryo-electron microscopy structure of the G. lamblia (WB strain) ribosome determined at 2.75 Å resolution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…Clear densities could be observed for all universal and eukaryote-specific r-proteins, except eL6, eL28, the P-stalk proteins, eS12, eS31 and RACK1 (Figure 1A ). It is known that the orthologs for eL6 and eL28 are missing in G. intestinalis ( 46 , 47 ), which we confirm by performing mass spectroscopic analysis (Supplementary Material, PDF Spreadsheet). Further, we have built the entire rRNA except the P stalk and some small parts of LSU in the vicinity of eL13 and uL29.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Clear densities could be observed for all universal and eukaryote-specific r-proteins, except eL6, eL28, the P-stalk proteins, eS12, eS31 and RACK1 (Figure 1A ). It is known that the orthologs for eL6 and eL28 are missing in G. intestinalis ( 46 , 47 ), which we confirm by performing mass spectroscopic analysis (Supplementary Material, PDF Spreadsheet). Further, we have built the entire rRNA except the P stalk and some small parts of LSU in the vicinity of eL13 and uL29.…”
Section: Resultssupporting
confidence: 74%
“…Although our knowledge about eukaryotic translation has developed a lot in recent years, studies investigating mechanisms of translation in unicellular parasitic eukaryotes are scarce. Structures of cytoplasmic ribosomes are available for Giardia lamblia ( 46 , 47 ), Trichomonas vaginalis ( 48 ), Trypanosoma brucei ( 49 , 50 ), Vairimorpha necatrix ( 51 ), Toxoplasma gondii ( 48 ) and Plasmodium falciparum ( 52 , 53 ), which present distinctive features compared to higher eukaryotic ribosomes. For example, G. lamblia , T. vaginalis and V. necatrix all have a highly reduced rRNA devoid of most eukaryote-specific expansion segments (ESs) ( 48 , 51 ), while T. brucei 28S rRNA has six fragments stabilized by species-specific ESs or ribosomal protein (r-protein) extensions ( 49 , 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these scenarios provide an opportunity for the cell to lose ESs and preserve precious resources. In parasitic eukaryotes, the ribosome reduction accompanied the global genome compaction, thus exemplifying a scenario of regressive evolution (Melnikov et al 2018;Barandun et al 2019;Hiregange et al 2022). However, the Saccharomycotina species including magnusiomycetes are free-living organisms and do not exhibit any apparent correlation between the genome size and the length of ESs (Figure 5) and, at the same time, we did not identify compensatory changes in the ribosomal protein inventories or ribosome-interacting partners clearly associated with the shortening of rRNAs.…”
Section: Reduction Of Ess Is Not Limited To Magnusiomyces/saprochaete...mentioning
confidence: 99%
“…Later, Wenman used the same method to confirm the distribution in the earthworm plasma membrane, and Feliziani demonstrated by immunohistochemical analysis that the Giardin-a-1 protein is mainly distributed in the cytoplasmic membrane of trophozoites [4]. And identified 14 additional α-Giardin genes (α-4, α-5, α-6, α-8 to α-13 and α-15 to α-19) by scanning the Giardia genome [5]; studies on the cellular localisation of the α-Giardin family also showed that α-3, α-5 and a-17 are distributed in the ventral suckers; α-15 and α-16 are distributed along the cell membrane; α-1, α-7.1. The remaining eight species (α-1, α-2, α-6, α-7.2 The remaining eight species (α-1, α-2, α-6, α-7.2, α-7.3, α-9, α-10, α-14) were mainly distributed in the cytoplasm, flagella or cell membrane of suckers, as they were overexpressed after transfection of trophozoites with recombinant vectors [3,6].…”
Section: Giardia Intestinalismentioning
confidence: 99%